Assessment of anxiety and quality of life in fibromyalgia patients - Pagano, Tathiana (2004)
CONTEXT: Fibromyalgia is a syndrome characterized by chronic, diffuse musculoskeletal pain, and by a low pain threshold at specific anatomical points. The syndrome is associated with other symptoms such as fatigue, sleep disturbance, morning stiffness and anxiety. Because of its chronic nature, it often has a negative impact on patients’ quality of life. OBJECTIVE: To assess the quality of life and anxiety level of patients with fibromyalgia. TYPE Of STUDY: Cross-sectional. SETTING: Rheumatology outpatient service of Hospital das Clínicas (Medical School, Universidade de São Paulo). METHODS: This study evaluated 80 individuals, divided between test and control groups. The test group included 40 women with a confirmed diagnosis of fibromyalgia. The control group was composed of 40 healthy women. Three questionnaires were used: two to assess quality of life (FIQ and SF-36) and one to assess anxiety (STAI). They were applied to the individuals in both groups in a single face-to-face interview. The statistical analysis used Student’s t test and Pearson’s correlation test (r), with a significance level of 95%. Also, the Pearson chi-squared statistics test for homogeneity, with Yates correction, was used for comparing schooling between test and control groups. RESULTS: There was a statistically significant difference between the groups (p = 0.000), thus indicating that fibromyalgia patients have a worse quality of life and higher levels of anxiety. The correlations between the three questionnaires were high (r = 0.9). DISCUSSION: This study has confirmed the efficacy of FIQ for evaluating the impact of fibromyalgia on the quality of life. SF-36 is less specific than FIQ, although statistically significant values were obtained when analyzed separately, STAI showed lower efficacy for discriminating the test group from the control group. The test group showed worse quality of life than did the control group, which was demonstrated by both FIQ and SF-36. Even though STAI was a less efficient instrument, it presented significant results, showing that fibromyalgia patients presented higher levels of anxiety, both on the state and trait scales. Thus, patients with fibromyalgia had higher levels of tension, nervousness, preoccupation and apprehension, and higher propensity towards anxiety. CONCLUSION: The three instruments utilized showed efficiency in evaluating fibromyalgia patients. FIQ was found to be the most efficient instrument for discriminating and assessing the impact of fibromyalgia on their quality of life. It can be concluded that such patients have a worse quality of life and higher levels of anxiety.